2017
DOI: 10.1111/jere.12148
|View full text |Cite
|
Sign up to set email alerts
|

Employment Status Persistence in the Japanese Labour Market

Abstract: The growth of non-standard employment has become a cause for concern for policymakers trying to boost output and keep unemployment low while also maintaining job security. This paper estimates a dynamic unobserved effects model using the Keio Household Panel Survey, an individual-level panel data set, to investigate the effects on future employment opportunities of employment in Japan's non-standard employment and regular employment sectors. I find strong evidence of persistence within the labour market, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…When employment status of a first job is nonstandard, it is negatively associated with the likelihood of later finding a standard employment position. This relationship seems to be robust in regard to social origins or educational attainment (Ishida 2005), and one's initial employment status is causally linked to later occupational trajectories (Diamond 2018;Genda et al 2010;Hamaaki et al 2013;Kondo 2007).…”
Section: Distinction By Employment Statusmentioning
confidence: 86%
See 1 more Smart Citation
“…When employment status of a first job is nonstandard, it is negatively associated with the likelihood of later finding a standard employment position. This relationship seems to be robust in regard to social origins or educational attainment (Ishida 2005), and one's initial employment status is causally linked to later occupational trajectories (Diamond 2018;Genda et al 2010;Hamaaki et al 2013;Kondo 2007).…”
Section: Distinction By Employment Statusmentioning
confidence: 86%
“…As such, it is not surprising that missing opportunities for standard employment in one's early stage of career constrains individuals' later labor market trajectories. Indeed, abundant studies have shown that nonstandard employment, especially as a first job, has enduring negative effects on a range of later outcomes (Diamond 2018;Genda et al 2010;Hamaaki et al 2013;Ishida 2005;Kondo 2007;Yu 2012). For instance, Yu (2012) has found that having a nonstandard job is associated with a lower chance of transitioning to standard employment, lower wages, and lower occupational prestige in later careers than those of the unemployed.…”
Section: Distinction By Employment Statusmentioning
confidence: 99%